Selective internal radiation therapy for hepatocellular carcinoma: A 15‐year multicenter Australian cohort study. Issue 11 (2nd September 2022) - Prince, David Stephen; Schlaphoff, Glen; Davison, Scott Anthony; Huo, Ya Ruth; Xiang, Hao; Chan, Michael Vinchill; Lee, Alice Unah; Thailakanathan, Cynthuja; Jebeili, Hazem; Rogan, Christopher; Al‐Omary, Ahmed; Gupta, Sidhartha; et al.
Abstract: Background and Aim: The exact place for selective internal radiation therapy (SIRT) in the therapeutic algorithm for hepatocellular carcinoma (HCC) is debated. There are limited data on its indications, efficacy, and safety in Australia. Methods: We performed a multicenter retrospective cohort study of patients undergoing SIRT for HCC in all Sydney hospitals between 2005 and 2019. The primary outcome was overall survival. Secondary outcomes were progression‐free survival and adverse events. Results: During the study period, 156 patients underwent SIRT across 10 institutions (mean age 67 years, 81% male). SIRT use progressively increased from 2005 ( n  = 2), peaking in 2017 ( n  = 42) before declining (2019: n  = 21). Barcelona Clinic Liver Cancer stages at treatment were A (13%), B (33%), C (52%), and D (2%). Forty‐four (28%) patients had tumor thrombus. After a median follow‐up of 13.9 months, there were 117 deaths. Median overall survival was 15 months (95% confidence interval 11–19). Independent predictors of mortality on multivariable analysis were extent of liver involvement, Barcelona Clinic Liver Cancer stage, baseline ascites, alpha fetoprotein, and model for end‐stage liver disease score. Median progression‐free survival was 6.0 months (95% confidence interval 5.1–6.9 months). Following SIRT, 11% of patients were downstaged to curative therapy. SIRT‐related complications occurred in 17%: radioembolization‐induced liver disease (11%), pneumonitis (3%), gastrointestinal ulceration, and cholecystitis (1% each). Baseline ascites predicted for radioembolization‐induced liver disease. Conclusion: We present the largest Australian SIRT cohort for HCC. We have identified several factors associated with a poor outcome following SIRT. Patients with early‐stage disease had the best survival with some being downstaged to curative therapy.